Economic feasibility of a utility-scale battery in Iceland - Nathanael Scott Rybin 1996- (2023)
Utility-scale batteries are gaining popularity due to their decreasing costs and are becoming increasingly crucial for integrating renewable energy sources. Batteries offer unique opportunities to reduce electricity usage costs and generate profits by providing various services. This study explores the potential of adding a battery to the Icelandic market by modeling the market’s response to the addition and estimating the potential revenue generated during the battery’s operation. The battery is modeled to operate in the primary, fast frequency response, and balancing markets, with each scenario outputting the potential revenue generated. Using the generated revenue and the current battery costs from literature, a financial analysis is conducted to determine the battery's net present value. The battery costs are also used to determine the minimum revenue required to break even on the investment. The results indicate that under current scenarios and electricity prices the battery is not profitable. So, an explanation is explored as to why the battery is not currently profitable in Iceland.